THE IMPACT OF LEACHING AND IRRIGATION TECHNOLOGY ON THE SALT BALANCE OF STRONGLY SALINIZED SOILS IN THE BUKHARA REGION - U. A. Juraev; B. N. Atamurodov; O. M. Yusupova (Web of Journals Publishing, 2025)
This article presents the results of field experiments on salt leaching and water-saving irrigation technology for cotton in the heavily saline, heavy loam soils of the long-irrigated alluvial meadows of Bukhara region. The study evaluates salt balance, with results showing that salt content decreased by 3.3 t ha-1 in the second variant and by 7 t ha-1 in the third variant compared to the control.
Keywords: Saline soils, deep loosening, perforated drainage, vegetation period, salt balance, salt leaching, cotton irrigation.